Paternalism as punishment - Birks, D (Cambridge University Press, 2020)
In this paper, I argue that even if we hold that at least some paternalistic behaviour is impermissible when directed towards innocent persons, in certain cases, the same behaviour is permissible when directed towards criminal offenders. I also defend the claim that in some cases it is morally preferable to behave paternalistically towards offenders as an alternative to traditional methods of punishment. I propose that the reason paternalistic behaviour is sometimes permissible towards an offender is the same reason that inflicting intentional harm on an offender is permissible — namely, that it is sometimes a morally justified method of punishing an offender for his wrongdoing.